Brain metastatic breast cancer: palliative or not? - Mohame Tahir, Mohamad Hafizzudin; Wan Omar, Wan Abdul Halim; Wahab, Mohd Ghaddafi; Mahno, Noor Ezmas (Faculty of Medicine, UKM, 2024)
Introduction: Breast cancer is the most common malignancy in females worldwide with 1 in 20 females over 70 years old diagnosed with it. Metastatic breast cancer in earlier years was treated palliatively but nowadays, with the rise of medical advances and technologies, a lot of options can be offered to those patients either by surgical, chemotherapy, radiotherapy, or immunotherapy. We reported 2 cases with breast cancer with symptomatic brain metastasis and successfully managed with surgical approach. Case 1: Madam F is a 54-year-old lady with T2N2M0 Right invasive ductal carcinoma of hormonal positive and HER2 overexpressed in 2021. She had right mastectomy and axillary clearance followed by adjuvant chemo-radiotherapy. She was started with adjuvant hormonal therapy since then. In September 2023, she had persistent headache subsequently found to have right occipital brain metastasis with ipsilateral axillary recurrence at the same time. We manage to proceed with right craniotomy and tumor debulking and subsequent adjuvant hormonal and brain radiotherapy. Case 2: A 36-year-old female presented in March 2021 with right locally advanced invasive ductal carcinoma T4N1M0. She had upfront neoadjuvant chemotherapy + pembrolizumab. She had complete pathological response and proceed with right mastectomy and axillary clearance followed by adjuvant chemotherapy and adjuvant pembrolizumab with chest wall radiotherapy. Three years later, she had increased intracranial pressure subsequently showed cerebellum tumor suggestive of metastasis. She had suboccipital craniotomy, right Frazier extra-ventricular drainage insertion and tumor debulking however the tumor recurred and currently on going second line chemotherapy. Conclusion: Approaching a patient with brain metastasis breast cancer is a challenge as deciding a surgical approach to control the disease progression and improving the overall survival in selected cases. Both cases show a promising result after a surgical treatment with aiming to improve the quality of life and aiming for better overall survival.